A Militancy of Invidious Comparisons: The Contested Value of Hospital Work in Ontario, 1959–1974 - Hurl, Chris (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2022)
This article examines the efforts to establish objective criteria in deciding on appropriate wage levels for non-professional service workers in Ontario’s hospital sector during the 1960s and 1970s. Drawing from recent literature in cultural political economy and the politics of valuation, it shows how industrial relations specialists sought to reframe the field of struggle through the practice of interest arbitration. Through a comparative study of arbitration cases in this period, the article explores the complex displacement of expertise from local hospital boards and medical professionals to law professors and labour economists, who sought to establish an industrial jurisprudence that could avoid strikes and lockouts in such essential industries by assigning awards based on the probable outcomes of industrial conflict. No longer were disputes settled through the ideological obfuscations of “justice”; instead, expert arbitrators drew on the science of economics in asserting irrefutable labour market “realities.” While pretensions to scientific expertise in the settlement of disputes remained hegemonic through the late 1960s, hospital workers in Ontario, through their unions and in alliance with New Left organizations, effectively reasserted “justice” as a highly contextualized unit of value through their militant struggles in the early 1970s. The article concludes by discussing the tensions and contradictions produced out of these struggles and the subsequent challenges in regulating public-sector labour disputes.